Role of placental inflammatory mediators and growth factors in patients with rheumatic diseases with a focus on systemic sclerosis. (13th December 2020) - Motta, Francesca; Codullo, Veronica; Ramoni, Véronique; Cesari, Stefania; Ferrario, Giuseppina; Fiandrino, Giacomo; Beneventi, Fausta; Rampello, Stefania; Johnsson, Hanna; Montecucco, Carlomaurizio; Graham, Gerard J
Abstract: Objectives: Pregnancy in SSc is burdened with an increased risk of obstetric complications. Little is known about the underlying placental alterations. This study aimed to better understand pathological changes and the role of inflammation in SSc placentas. Leucocyte infiltration, inflammatory mediators and atypical chemokine receptor 2 (ACKR2) expression in SSc placentas were compared with those in other rheumatic diseases (ORD) and healthy controls (HC). Methods: A case–control study was conducted on eight pregnant SSc patients compared with 16 patients with ORD and 16 HC matched for gestational age. Clinical data were collected. Placentas were obtained for histopathological analysis and immunohistochemistry (CD3, CD20, CD11c, CD68, ACKR2). Samples from four SSc, eight ORD and eight HC were analysed by qPCR for ACKR2 expression and by multiplex assay for cytokines, chemokines and growth factors involved in angiogenesis and inflammation. Results: The number of placental CD3, CD68 and CD11 cells was significantly higher in patients affected by rheumatic diseases (SSc+ORD) compared with HC. Hepatocyte growth factor was significantly increased in the group of rheumatic diseases patients (SSc+ORD) compared with HC, while chemokine (C-C motif) ligand 5 (CCL5) was significantly higher in SSc patients compared with ORD and HC. CCL5 levels directly correlated with the number of all local inflammatory cells and higher levels were associated with histological villitis. Conclusions: Inflammatory alterations characterize placentas from rheumatic disease patients and could predispose to obstetric complications in these subjects.